(untitled) (African Journal of Biomedical Research, 2019)
While plants have been useful to man as food and medicine, many have the potentials to induce toxicity either singly or in combination, which may result from their phytochemical contents or accumulation of toxic metals. Therefore, this study investigated the metal contents and acute toxicity of Vernonia amygdalina (VA) leaves and Garcinia kola (GK) seeds in single and combined forms on rat′s kidney and liver. Aqueous extracts of these plants were used to investigate their acute toxicity potentials separately and in combined formulation, VAGK, using male Wistar rats. Following previous studies, a limit acute toxicity investigation of VA and GK were carried out. In addition, a full acute toxicity test was performed on VAGK using Lorkes’ method. The geometric means of doses were used to obtain the acute toxicity value. Histopathological examination was carried out on harvested rats’ kidney and liver while metal analysis was performed on the powdered plants. Results showed that all animals survived the limit dose as well as the full acute toxicity tests. The Kidney and liver revealed no notable pathological changes in the tested plants. Concentration of some of the analysed metals (mg/kg) in plants fell within recommended permissible limits except for Pb, Co, Cr and Ni, which were above these limits. In conclusion, although the acute oral toxicity test revealed no mortality and demonstrated no detrimental effects on the kidney and liver of the treated rats, however based on metal results, caution must be taken when using these plants as herbal remedy.